Cervical effacement, as an independent parameter versus modified bishop score, for predicting the favorability of vaginal delivery in a primigravida at 40 weeks gestation and beyond - Galzie, Saniyah Khan; Rao, Smitha B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Dr. Edward Bishop developed the original bishop score. He concluded that elective induction in multiparous women was successful with a score > 8. Calder introduced the modified bishop score in which he replaced cervical effacement with cervical length in cms. Score of 6-12 is favourable. In this study, studied the cervical effacement/ length as an independent predictor of vaginal delivery in a primigravida. Methods: A retrospective observational study was conducted from May 2018 to January 2019. Total participants were divided into two groups on the basis of spontaneous labor and induced labor. Both the groups were assessed individually and collectively in terms of cervical effacement/length and modified bishop score. Study primary outcome was vaginal delivery. The results were reflected in terms of sensitivity, specificity, PPV and NPV. These values were compared for cervical effacement/ length as well as modified bishop score and p value calculated. Also, association between modified bishop score and cervical effacement/length was established. Results: Total number of participants included was n = 91. Those with modified bishop score > 6, 78.16% had vaginal delivery. This gave a sensitivity of 78.16%, specificity of 50%, PPV of 97.14%. Those with cervical effacement of >/=50% or cervical length of </= 2 cms, 78.82% had vaginal delivery. This gave a sensitivity of 78.82%, specificity of 55%, PPV of 95.71%. Thus, it had similar sensitivity, specificity, PPV to that of modified bishop score, and therefore has the same accuracy in predicting vaginal delivery. Also, 89.01% participants who had cervical effacement >/= 50% had modified bishop score >/= 6, reflecting the association between them. Conclusions: Cervical effacement of >/= 50% or cervical length </= 2 cms yielded an equivalently high predictive ability similar to modified bishop score, for spontaneous as well as induced labor. Hence, cervical effacement can be taken as an independent parameter to assess the favorability of successful vaginal delivery in a primigravida.